2012
DOI: 10.1007/s00595-012-0407-2
|View full text |Cite
|
Sign up to set email alerts
|

Margin-negative limited resection of metastatic pancreatic tumors from rectal cancer preoperatively diagnosed by endoscopic ultrasound-guided fine-needle aspiration biopsies: report of two cases

Abstract: Pancreatic tumor metastasis from colorectal cancer is very rare. This study evaluated the significance of an endoscopic ultrasound-guided fine-needle aspiration biopsy (EUS-FNAB) and surgical treatment. Case 1 was a 67-year-old male with a history of rectal cancer (6 years ago) and lung metastases (5 years ago) who had two masses in the pancreatic head and body. Case 2 was a 58-year-old male with the history of rectal cancer and simultaneous lung metastasis (7 years ago) who had a mass in the pancreatic body. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Twenty-eight patients presented with single pancreatic metastasis; in 9 cases additional surgery was required to treat metastatic disease in other sites. In some case reports on pancreatic metastasis from rectal cancer, a history of metachronous pulmonary metastasis prior to the diagnosis of pancreatic lesions was reported (3,4,16,17). Inagaki et al (3) suggested that pulmonary tumors may metastasize to the pancreas by hematogenous spread.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Twenty-eight patients presented with single pancreatic metastasis; in 9 cases additional surgery was required to treat metastatic disease in other sites. In some case reports on pancreatic metastasis from rectal cancer, a history of metachronous pulmonary metastasis prior to the diagnosis of pancreatic lesions was reported (3,4,16,17). Inagaki et al (3) suggested that pulmonary tumors may metastasize to the pancreas by hematogenous spread.…”
Section: Discussionmentioning
confidence: 99%
“…However, more recently, several reports have been published regarding the use of EUS-FNA in the diagnosis of pancreatic metastases (4,7-11). In the diagnosis of pancreatic metastases, the sensitivity, specificity, positive and negative predictive values, and the accuracy of the histological analysis of EUS-FNA specimens are reported to be 93.8%, 60%, 93.8%, 60%, and 89%, respectively (11).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[23,29,30] In our current series, the major indications were metastatic tumors of the pancreas, including renal cell carcinoma (RCC), DFSP, and pheochromocytoma. The most common origin of pancreatic metastatic tumor reported in the literature is RCC; others include breast cancer, lung cancer, colonic cancer, and melanoma.…”
Section: Discussionmentioning
confidence: 99%